Thin films of cross-linked metallo-supramolecular coordination polyelectrolytes - Sievers, Torsten K (Langmuir : the ACS journal of surfaces and colloids, 2007)
We report on the synthesis of a new tristerpyridine ligand, tris(2,2':6',2' '-terpyridinyl-4'-oxymethyl)ethane (tritpy), as well as its introduction into metal ion induced self-assembly of cross-linked metallo-supramolecular coordination polyelectrolytes (MEPE). For cross-linking degrees of 9.5% and below, soluble homogeneous networks are obtained. The molar mass of the networks is large and depends on the cross-linking degree. Due to the charges in the MEPE, the soluble networks are suitable for film formation on the basis of layer-by-layer self-assembly and to study the details of film growth. UV-vis spectroscopy, X-ray reflectivity, AFM, and ellipsometry show that the film growth is linear and continuous. The multilayers exhibit no inner structure and have a very low surface roughness. The thickness of the adsorbed layer of MEPE networks is in the range of 3 nm. The important point is that an influence of cross-linking is not seen in multilayers, which is the opposite of what is observed for the MEPE in solution. Our experiments did not reveal an influence of the preparation procedure on the adsorption process, e.g., increasing the layer thickness